Le minimalisme dans l’éthique de la discussion - Pierre Billouet (Recherches en Éducation)
The moral Minimalism and the Discourse ethics dispute the paternalism of the authorities which claim to do good of subordinates without asking them to anything. But the precise examination of their principles, on one hand, and the understanding of the theory of Kohlberg of the moral development on the other hand, allows to show that there is a profound difference between both approaches. The concept of the autonomy is the touchstone allowing to decide between both ethics, the educational and political consequences of which cannot be identified.